Educational action with high school adolescents: a reflection on self-image and food disorders (Research, Society and Development, 2020)
The way the individual perceives his own body is modified over time, and this occurs more intensely during adolescence. Body dissatisfaction is highlighted as one of the important factors considered for the diagnosis of eating disorders and is also one of the triggers for their occurrence. Thus, the following study aims to report a health education experience carried out with adolescents from a Professional High School in a municipality of Maciço de Baturité, geological formation located in the central hinterland of Ceará, addressing the theme of body self-image and its implications for the occurrence of Eating Disorders. The activity took place through stages that contained dynamics of interaction and introduction of the theme, as well as approaching the content in a dialogical way. Given the above, there are still deficits in addressing the theme in the school environment and in other environments in which the adolescent is inserted. Therefore, the role of educational sectors allied to health are perceived as areas that must be articulated in order to guarantee greater support and assistance to young people and their families, characterizing the performance of the multiprofessional team in the aspect of psychosocial care.